Bio-fertilizers application in agricultural biotechnology - Mohamed, Elizah; Mohd Adnan, Nuraisha Syazwani; Abd Talib, Nur Idayu (Penerbit UTHM, 2022)
Nutrient supplementation of soil is important as the soil is the medium for the plants for growth as the soil supplies the nutrients needed by the plants. It includes phosphorus, nitrogen and potassium. In the meantime, the farmers use chemical fertilizers in order to increase the fertility of the soil. However, the uses of chemical fertilizer have given many effects to the environment and also society as it increases the nitrogen content which will cause a decrease in the colonization of plant roots of mycorrhizae and prevent the rhizobacteria from fixing the nitrogen. As the cause of that, it continuously will reduce the soil fertility which also reduces the productivity crop yield for the farmers. New technology in the agricultural sector that uses renewable and eco-friendly bio-fertilizers have become a new approach to the researchers and to the farmers as other alternatives in increasing the nutrient content in the soil. The formation of biofertilizers can be obtained from several sources of microorganisms such as azospirillum, azolla, arbuscular mycorrhizal fungi, rhizobium, azotobacter, silicate solubilizing bacteria cyanobacteria, phosphate solubilizing microorganisms, and plants growth promoting rhizobacteria. The bio-fertilizer also can be classified into several types according to its function and purposes which is phosphate solubilizing bio-fertilizers, nitrogen fixing biofertilizers, micro-nutrients phosphate mobilizing bio-fertilizers, and plants growth promoting rhizobacteria. Bio-fertilizers can be performed using different methods such as seed treatments, seedling root dip, soil treatment, VAM bio-fertilizers, blue green algae, azolla, pH, electrical conductivity, organic carbon, nitrogen and phosphorus. The use of bio-fertilizer has become a preferable biofertilizer in replacing the use of chemical fertilizers. It gives many benefits and advantages in sustainability and reasonable prices, as it improves the soil fertility towards the plant productivity. As it has positive effects on the plants and environment, at the same time, it also gives effects to society as it has the ability to increase the market production of products which at the same time will reduce the negative effects on the people and society. As the bio-fertilizers increase crop productivity, it will give a higher potential to provide larger and more sustainable yields and healthier soils for the society, especially for the small-scale farmers. In fact, bio-fertilizers have become a new way to develop crop yield productivity. There are great renewable products that can be used to have a better life in the future to achieve sustainability. This chapter will be focused on the application of bio-fertilizer in agricultural biotechnology.